Memory as an “unknown life form”: W. G. Sebald and the Contemporary Balkan novel (or once again about the museum structured novel) (Colloquia Comparativa Litterarum, 2025)
The article is a kind of “return” to the double optics of the concept concerning the museum in literature and literature in the use of the museum – the museum as a specific narrative model, but also as a cultural metaphor. This is an attempt to trace the possible points of “intersection” between the works of W. G. Sebald and selected novels by contemporary Balkan writers, such as Andreea Răsuceanu, Antonis Georgiu and Galin Nikiforov. The focus of the study is on the museum's “archiving” function to include different narrative forms in the genre of the novel. The comparative analysis highlights the visual transformations of memory in the form of album/diary/home/temple which constructs a space independent of time and marked by enormous narrative potential in the museum structured novel.
Keywords: W.G. Sebald; Andreea Răsuceanu; Antonis Georgiu; memory; museum structured novel; album; diary